Comparison of Biomasses of Different Plants for Phytoremediation of Arsenic - TASKEEN, ABIDA; NAEEM, ISMAT; MUBEEN, HIFSA; MOEEN, TAHIRA (Asian Journal of Chemistry, 2010)
The removal of heavy metals from drinking water, lake and waste water is crucial issue concern to health. The brake fern, Pteris vittata, is claimed to be the first found to function as an arsenic hyper accumulator. Phytoremediation by water hyacinth presents a potential solution to the arsenic problem. In the present study three plants (Calotropis procera, Eichhoenia crassipes and Pteris vittata) biomasses are selected and there arial parts and roots (dry biomasses) are compared for the first time. Also these plants are checked for the presence of other metals. After the removal of metal the treated water is then checked for the drinking water parameters. It was found that roots of Calotropis procera are best of biomasses selected for the phytoremediation of arsenic. The capacity of removal of Calotropis roots was also determined. After treatment water samples meet all EPA standards for drinking water.